TRIM26 Induces Ferroptosis to Inhibit Hepatic Stellate Cell Activation and Mitigate Liver Fibrosis Through Mediating SLC7A11 Ubiquitination - Zhu, Yiming; Zhang, Chihao; Huang, Mingzhe; Lin, Jiayun; Fan, Xiao; Ni, Tao (Frontiers in Cell and Developmental Biology, 2021)
Hepatic stellate cells (HSCs) are activated by inflammatory mediators to secrete extracellular matrix for collagen deposition, leading to liver fibrosis. Ferroptosis is iron- and lipid hydroperoxide-dependent programmed cell death, which has recently been targeted for inhibiting liver fibrogenic processes. Tripartite motif-containing protein 26 (TRIM26) is an E3 ubiquitin ligase that functions as a tumor suppressor in hepatocellular carcinoma, while little is known about its function in liver fibrosis. In the present study, the differential expression of TRIM26 in normal and fibrotic liver tissues was examined based on both online databases and specimens collected from patient cohort. The effects of TRIM26 on HSC ferroptosis were examined in vitro through evaluating cell proliferation, lipid peroxidation, and expression of key ferroptosis-related factors. In vivo function of TRIM26 in liver fibrosis was examined based on CCl4-induced mice model. We found that TRIM26 was downregulated in fibrotic liver tissues. The overexpression of TRIM26 inhibited HSC proliferation, promoted lipid peroxidation, manipulated ferroptosis-related factor expressions, and counteracted the effect of iron inhibitor deferoxamine. Moreover, TRIM26 physically interacted with solute carrier family-7 member-11 (SLC7A11), a critical protein for lipid reactive oxygen species scavenging, and mediated its ubiquitination. In addition, TRIM26 overexpression induced HSC ferroptosis and mitigated CCl4-induced liver fibrosis in mice. In conclusion, TRIM26 promotes HSC ferroptosis to suppress liver fibrosis through mediating the ubiquitination of SLC7A11. The TRIM26-targeted SLC7A11 suppression can be a novel therapeutic strategy for liver fibrosis.